2023
DOI: 10.1111/joes.12548
|View full text |Cite
|
Sign up to set email alerts
|

Loan‐to‐value limits as a macroprudential policy tool: Developments in theory and practice

Abstract: I analyze the development of the loan‐to‐value (LTV) ratio limit for households as a macroprudential policy tool in both theory and practice, by surveying theoretical and empirical literature. I argue that the practical implementation of LTV caps preceded theoretical studies, but research has caught up since the global financial crisis, including research on which indicators seem to work best in flagging a potential future crisis. In practice, LTV ratio limits tend to be effective tools in buffering credit and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 120 publications
(224 reference statements)
0
1
0
Order By: Relevance
“…Norway introduced LTV regulations in 2010 by implementing amortization requirements on loans with LTV above 60 % and establishing an upper limit on LTV of 85 %. According to Gatt (2023), such regulations have been successful in several countries but require fine-tuning and increased knowledge. Böhnke et al (2023) observed that over the last decades, Norway combines low country risk, a stable regulatory environment, high profitability, and high capital levels relative to the estimated risk in banks' portfolios, and Reite et al (2022) reported that the real estate market had large differences in centrality and steadily rising housing prices and a housing market that recovered within a year of the 2008 financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Norway introduced LTV regulations in 2010 by implementing amortization requirements on loans with LTV above 60 % and establishing an upper limit on LTV of 85 %. According to Gatt (2023), such regulations have been successful in several countries but require fine-tuning and increased knowledge. Böhnke et al (2023) observed that over the last decades, Norway combines low country risk, a stable regulatory environment, high profitability, and high capital levels relative to the estimated risk in banks' portfolios, and Reite et al (2022) reported that the real estate market had large differences in centrality and steadily rising housing prices and a housing market that recovered within a year of the 2008 financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…There is mixed evidence on the effects of borrower-based measures on credit and house prices. For example, the literature review by Gatt (2023) concludes that the evidence on a link between LTV caps and credit is 'suggestive.' Specifically, borrower-based measures seem to have weaker effects in advanced economies (AEs) and stronger effects when they are first introduced than when they are subsequently tightened.…”
mentioning
confidence: 99%
“…Landvoigt, Piazzesi, and Schneider (2015) find that cheaper credit for poor households was a major driver of prices in San Diego County during the 2000s boom, especially at the low end of the market. Mortgage debt can be constrained by financial policies such as loan-to-value caps (Gatt 2023), which may therefore help resolve housing shortages, quite apart from house building and monetary policies 4 .…”
Section: The Nature Of Shortagesmentioning
confidence: 99%